Organic silicon pouring sealant as well as preparation method and application thereof
By combining specific formulas and the preparation method of modified potassium titanate whiskers in silicone potting, the problems of insufficient thermal conductivity and adhesion properties of traditional potting are solved, and efficient electronic components and optics are achieved. Device sealing and heat dissipation management.
Patent Information
- Application Number
- CN202411507354.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional silicone potting glue has poor thermal conductivity and is difficult to meet the heat dissipation needs of high-power electronic equipment. At the same time, the bonding performance cannot be guaranteed after the thermal conductivity filler increases.
Using a formula of silicone potting adhesive, including matrix resin, plasticizer, multi-wall carbon nanotubes, modified potassium titanate whiskers, crosslinking agents and coupling agents, through specific viscosity ratios and preparation methods, Form excellent thermal conductivity and bonding properties.
It achieves efficient thermal conductivity and bonding performance, can be effectively applied to the sealing of electronic components and optical devices, improves the durability and stability of potting, and ensures sealing effect and heat dissipation performance.
Smart Images

Figure BDA0005104378410000111 
Figure BDA0005104378410000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of potting adhesives, and in particular to an organosilicon potting adhesive and a preparation method and application thereof. Background Art
[0002] As an important electronic packaging material, silicone potting compound is widely used in the fields of electronics, electrical appliances, automobiles, aerospace, etc. With the widespread application of electronic equipment and high-performance electrical appliances, the integration and power density of electronic components are constantly improving. In a high-power, high-density operating environment, electronic components generate a lot of heat during operation. If the heat cannot be dissipated in a timely and effective manner, it will cause the equipment to overheat, affecting its performance and service life, and even causing safety hazards. Therefore, potting materials with excellent thermal conductivity play a vital role in the heat dissipation management of electronic components.
[0003] Silicone potting compounds have been widely used in the packaging of electronic components due to their excellent heat resistance, insulation, aging resistance and flexibility. However, the thermal conductivity of traditional silicone potting compounds is poor, usually below 2W / m·K, which makes it difficult to meet the heat dissipation requirements of high-power electronic devices. In addition, the bonding performance of existing potting compounds cannot be guaranteed after the amount of thermal conductive filler added increases.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a silicone potting adhesive and a preparation method and application thereof. The silicone potting adhesive has excellent thermal conductivity and bonding properties and can be effectively used for sealing electronic components and optical devices.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] An organic silicon potting adhesive comprises the following components in parts by weight: 100 parts of a base resin, 15 to 22 parts of a plasticizer, 8 to 12 parts of multi-walled carbon nanotubes, 12 to 18 parts of modified potassium titanate whiskers, 3 to 6 parts of a crosslinking agent, 1 to 4 parts of a coupling agent, and 0.1 to 0.5 parts of a catalyst;
[0008] The base resin comprises a first alkoxy-terminated polydimethylsiloxane, a second alkoxy-terminated polydimethylsiloxane and a methyl vinyl MQ resin in a mass ratio of (6-8):(1-3):1;
[0009] The viscosity of the first alkoxy-terminated polydimethylsiloxane is AmPa·s, and the viscosity of the second alkoxy-terminated polydimethylsiloxane is BmPa·s, satisfying 6≤A / B≤20.
[0010] As a preferred embodiment of the present invention, the viscosity of the first alkoxy-terminated polydimethylsiloxane at 25° C. is 10000 to 20000 mPa·s.
[0011] As a preferred embodiment of the present invention, the viscosity BmPa·s of the second alkoxy-terminated polydimethylsiloxane at 25° C. is 1000 to 1500 mPa·s.
[0012] As a preferred embodiment of the present invention, the viscosity of the methyl vinyl MQ resin at 25° C. is 10000 to 15000 mPa·s.
[0013] As a preferred embodiment of the present invention, the plasticizer is dimethyl silicone oil, and the viscosity of the dimethyl silicone oil at 25° C. is 350 to 700 mPa·s.
[0014] As a preferred embodiment of the present invention, the outer diameter of the multi-walled carbon nanotubes is 10 to 20 nm, and the length is 10 to 30 μm.
[0015] As a preferred embodiment of the present invention, the preparation method of the modified potassium titanate whisker is:
[0016] (1) stirring potassium titanate whiskers, tartaric acid and nitric acid solution to obtain a mixed solution;
[0017] (2) adding γ-acryloxypropyltrimethoxysilane to the mixed solution, stirring evenly at 50-70° C. to obtain a precursor solution;
[0018] (3) adding 1,3,5,7-tetramethylcyclotetrasiloxane, 8-chloro-1-octene, octamethylcyclotetrasiloxane and trifluoromethanesulfonic acid to toluene, stirring and reacting at 70-85° C. for 2-5 hours to obtain a modified solution;
[0019] (4) Add the modified liquid to the precursor liquid, stir evenly at 55-65° C., filter, and dry to obtain modified potassium titanate whiskers.
[0020] As a preferred embodiment of the present invention, the weight ratio of the potassium titanate whisker, tartaric acid, and nitric acid solution is 1: (0.1-0.2): (4-10);
[0021] The weight ratio of the γ-acryloxypropyltrimethoxysilane to the mixed liquid is (0.02-0.05):1;
[0022] The weight ratio of 1,3,5,7-tetramethylcyclotetrasiloxane, 8-chloro-1-octene, octamethylcyclotetrasiloxane, trifluoromethanesulfonic acid and toluene is 1: (0.5-2): (0.2-0.6): (0.05-0.2): (4-10);
[0023] The weight ratio of the modifying liquid to the precursor liquid is 1:(4-6).
[0024] As a preferred embodiment of the present invention, the crosslinking agent includes at least one of methyl tributylacetoximate silane, phenyl tributylacetoximate silane, and methyl vinyl dibutyl ketone oxime silane;
[0025] The catalyst includes at least one of dibutyltin dilaurate, dibutyltin diacetate, and stannous octoate;
[0026] The coupling agent includes at least one of γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.
[0027] The present invention also provides a method for preparing an organic silicon potting adhesive, comprising the following steps:
[0028] The base resin, plasticizer and cross-linking agent are mixed evenly, and then multi-walled carbon nanotubes and modified potassium titanate whiskers are added and mixed evenly. Finally, a coupling agent and a catalyst are added and mixed evenly to obtain an organic silicone potting adhesive.
[0029] The present invention also provides an application of the organic silicon potting adhesive in electronic components and optical devices.
[0030] The beneficial effects of the present invention are as follows: (1) the potting compound of the present invention has excellent thermal conductivity and bonding properties, and can be effectively used for sealing electronic components and optical devices; (2) the present invention uses two alkoxy-terminated polydimethylsiloxanes of different viscosities (the viscosity relationship satisfies 6≤A / B≤20), wherein the low-viscosity alkoxy-terminated polydimethylsiloxane improves the fluidity and wettability of the potting compound (promotes the dispersion of other components, especially fillers, in the system), improves the processing performance, makes it easier to mix, coat and cure, and improves the dispersion of other components in the system. Compatibility, and make it easier to penetrate into tiny gaps to ensure the sealing effect; high-viscosity alkoxy-terminated polydimethylsiloxane has higher cohesive strength and adhesion, promotes the formation of a denser cross-linked network structure, enhances the durability and stability of the potting compound, and prevents the potting compound from falling off or cracking when subjected to external forces; methyl vinyl MQ resin provides cross-linking points, promotes the formation of a denser cross-linked network structure, improves the heat resistance and stability of the potting compound, and further improves the fluidity of the system, so that the three are combined to effectively improve the thermal conductivity and adhesion properties of the system. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0032] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0033] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0034] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0035] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.
[0036] The raw materials used in the examples and comparative examples are described as follows:
[0037] Alkoxy-terminated polydimethylsiloxane-1: viscosity at 25°C is 10000 mPa·s, Jiangxi Kexing New Materials, brand F-10A.
[0038] Alkoxy-terminated polydimethylsiloxane-2: viscosity at 25°C is 20,000 mPa·s, Jiangxi Kexing New Materials, brand J-200.
[0039] Alkoxy-terminated polydimethylsiloxane-3: viscosity at 25°C is 1000 mPa·s, Jiangxi Kexing New Materials, brand F-01A.
[0040] Alkoxy-terminated polydimethylsiloxane-4: viscosity at 25°C is 1500 mPa·s, Jiangxi Kexing New Materials, brand J-15.
[0041] Alkoxy-terminated polydimethylsiloxane-5: viscosity at 25°C is 35000 mPa·s, Jiangxi Kexing New Materials, brand F-40A.
[0042] Methyl vinyl MQ resin-1: viscosity at 25°C is 10000-15000 mPa·s, Wynca Co., Ltd., brand Wynca-5322B.
[0043] Methyl vinyl MQ resin-2: viscosity at 25°C is 4500-7500 mPa·s, Wynca Co., Ltd., brand name Wynca-5322A.
[0044] Methyl vinyl MQ resin-3: viscosity at 25°C is 50,000-100,000 mPa·s, Wynca Co., Ltd., brand name Wynca-5322C.
[0045] Dimethyl silicone oil-1: viscosity at 25°C is 350 mPa·s, Zhejiang Rongli High-tech, brand 201-350.
[0046] Dimethyl silicone oil-2: viscosity at 25°C is 700mPa·s, Zhejiang Rongli High-tech, brand 201-700.
[0047] Dimethyl silicone oil-3: viscosity at 25°C is 100 mPa·s, Zhejiang Rongli High-tech, brand number 201-100.
[0048] Dimethyl silicone oil-4: viscosity at 25°C is 1000mPa·s, Zhejiang Rongli High-tech, brand 201-1000.
[0049] Multi-walled carbon nanotube-1: outer diameter is 10-20 nm, length is 10-30 μm, Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, brand TNMH3.
[0050] Multi-walled carbon nanotube-2: outer diameter 30-50 nm, length <10 μm, Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, brand TNMH7.
[0051] Multi-walled carbon nanotube-3: outer diameter 4-8 nm, length 0.5-2 μm, Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, brand TNSMH0.
[0052] Potassium titanate whiskers: length 0.2~8μm, diameter 0.1~2μm, Shanghai Fengzhu Composite New Materials, brand NP-TW4.
[0053] Crosslinking agent: methyl tributylidene silane.
[0054] Catalyst: dibutyltin dilaurate.
[0055] Coupling agent: γ-glycidyloxypropyltrimethoxysilane.
[0056] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0057] The embodiment of the present application provides a silicone potting compound, comprising the following components in parts by weight: 100 parts of a base resin, 15 to 22 parts of a plasticizer, 8 to 12 parts of multi-walled carbon nanotubes, 12 to 18 parts of modified potassium titanate whiskers, 3 to 6 parts of a cross-linking agent, 1 to 4 parts of a coupling agent, and 0.1 to 0.5 parts of a catalyst;
[0058] The base resin comprises a first alkoxy-terminated polydimethylsiloxane, a second alkoxy-terminated polydimethylsiloxane and a methyl vinyl MQ resin in a mass ratio of (6-8):(1-3):1;
[0059] The viscosity of the first alkoxy-terminated polydimethylsiloxane is AmPa·s, and the viscosity of the second alkoxy-terminated polydimethylsiloxane is BmPa·s, satisfying 6≤A / B≤20.
[0060] The present invention creatively combines the above-mentioned raw materials to obtain a material having excellent thermal conductivity and bonding properties, and can be effectively used in the sealing of electronic components and optical devices.
[0061] Among them, the present invention creatively adopts two alkoxy-terminated polydimethylsiloxanes of different viscosities (the viscosity relationship satisfies 6≤A / B≤20), wherein the low-viscosity alkoxy-terminated polydimethylsiloxane improves the fluidity and wettability of the potting glue (promotes the dispersion of other components, especially fillers in the system), improves the processing performance, makes it easier to mix, coat and cure, improves the compatibility of other components in the system, and makes it easier to penetrate into tiny gaps to ensure the sealing effect; the high-viscosity alkoxy-terminated polydimethylsiloxane has higher cohesive strength and bonding force, promotes the formation of a denser cross-linked network structure, enhances the durability and stability of the potting glue, and prevents the potting glue from falling off or cracking when subjected to external forces; the methyl vinyl MQ resin provides cross-linking points, promotes the formation of a denser cross-linked network structure, improves the heat resistance and stability of the potting glue, and further improves the fluidity of the system, so that the three are combined to effectively improve the thermal conductivity and bonding properties of the system.
[0062] In one embodiment, the viscosity of the first alkoxy-terminated polydimethylsiloxane at 25° C. is 10,000 to 20,000 mPa·s.
[0063] In one embodiment, the viscosity BmPa·s of the second alkoxy-terminated polydimethylsiloxane at 25° C. is 1000-1500 mPa·s.
[0064] In one embodiment, the viscosity of the methyl vinyl MQ resin at 25° C. is 10,000 to 15,000 mPa·s.
[0065] In particular, when the viscosity of the first alkoxy-terminated polydimethylsiloxane, the second alkoxy-terminated polydimethylsiloxane, and the methyl vinyl MQ resin is within the above range, the compatibility of the formula is better, the dispersion of other components in the system can be improved, and agglomeration can be avoided. At the same time, a dense cross-linked network structure is formed to prevent the potting glue from falling off or cracking when subjected to external forces, and the filler (multi-walled carbon nanotubes and modified potassium titanate whiskers) components are promoted to form a thermally conductive network structure, thereby further improving the thermal conductivity and bonding properties of the system.
[0066] In one embodiment, the plasticizer is dimethyl silicone oil, and the viscosity of the dimethyl silicone oil at 25° C. is 350 to 700 mPa·s.
[0067] In one embodiment, the multi-walled carbon nanotubes have an outer diameter of 10 to 20 nm and a length of 10 to 30 μm.
[0068] In one embodiment, the preparation method of the modified potassium titanate whisker is:
[0069] (1) stirring potassium titanate whiskers, tartaric acid and nitric acid solution to obtain a mixed solution;
[0070] (2) adding γ-acryloxypropyltrimethoxysilane to the mixed solution, stirring evenly at 50-70° C. to obtain a precursor solution;
[0071] (3) adding 1,3,5,7-tetramethylcyclotetrasiloxane, 8-chloro-1-octene, octamethylcyclotetrasiloxane and trifluoromethanesulfonic acid to toluene, stirring and reacting at 70-85° C. for 2-5 hours to obtain a modified solution;
[0072] (4) Add the modified liquid to the precursor liquid, stir evenly at 55-65° C., filter, and dry to obtain modified potassium titanate whiskers.
[0073] The invention improves the interface compatibility between the potassium titanate whisker and the substrate by modifying the potassium titanate whisker, reduces the gaps and defects at the interface, effectively reduces the thermal resistance, enables the whisker surface to have the ability to be chemically and physically combined with the substrate, can be evenly dispersed in the system without agglomeration, avoids the stress point concentration phenomenon of the potting glue, forms a continuous and effective heat conduction network with the multi-walled carbon nanotubes in the system, and simultaneously the network structure formed by the modified potassium titanate whisker and the multi-walled carbon nanotubes can also disperse and withstand external forces, thereby improving the bonding strength of the potting glue.
[0074] In one embodiment, the weight ratio of the potassium titanate whiskers, tartaric acid, and nitric acid solution is 1: (0.1-0.2): (4-10);
[0075] The weight ratio of the γ-acryloxypropyltrimethoxysilane to the mixed liquid is (0.02-0.05):1;
[0076] The weight ratio of 1,3,5,7-tetramethylcyclotetrasiloxane, 8-chloro-1-octene, octamethylcyclotetrasiloxane, trifluoromethanesulfonic acid and toluene is 1: (0.5-2): (0.2-0.6): (0.05-0.2): (4-10);
[0077] The weight ratio of the modifying liquid to the precursor liquid is 1:(4-6).
[0078] In one embodiment, the crosslinking agent includes at least one of methyl tributylacetoximate silane, phenyl tributylacetoximate silane, and methyl vinyl dibutyl ketone oxime silane;
[0079] The catalyst includes at least one of dibutyltin dilaurate, dibutyltin diacetate, and stannous octoate;
[0080] The coupling agent includes at least one of γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.
[0081] An embodiment of the present application provides a method for preparing a silicone potting compound, comprising the following steps:
[0082] The base resin, plasticizer and cross-linking agent are mixed evenly, and then multi-walled carbon nanotubes and modified potassium titanate whiskers are added and mixed evenly. Finally, a coupling agent and a catalyst are added and mixed evenly to obtain an organic silicone potting adhesive.
[0083] An embodiment of the present application provides an application of a silicone potting compound in electronic components and optical devices.
[0084] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.
[0085] Example 1
[0086] A silicone potting adhesive comprises the following components in parts by weight: 100 parts of base resin, 20 parts of dimethyl silicone oil-1, 10 parts of multi-walled carbon nanotube-1, 16 parts of modified potassium titanate whiskers, 5 parts of a crosslinking agent, 2 parts of a coupling agent, and 0.4 parts of a catalyst.
[0087] The base resin comprises alkoxy-terminated polydimethylsiloxane-1, alkoxy-terminated polydimethylsiloxane-4 and methyl vinyl MQ resin-1 in a mass ratio of 7:2:1.
[0088] The preparation method of the modified potassium titanate whisker is:
[0089] (1) stirring potassium titanate whiskers, tartaric acid and 1 mol / L nitric acid solution at a speed of 500 rpm to obtain a mixed solution; the weight ratio of the potassium titanate whiskers, tartaric acid and nitric acid solution is 1:0.15:8;
[0090] (2) adding γ-acryloxypropyltrimethoxysilane to the mixed solution, stirring at 60° C. and 500 rpm to obtain a precursor solution; the weight ratio of the γ-acryloxypropyltrimethoxysilane to the mixed solution is 0.04:1;
[0091] (3) adding 1,3,5,7-tetramethylcyclotetrasiloxane, 8-chloro-1-octene, octamethylcyclotetrasiloxane, and trifluoromethanesulfonic acid to toluene, stirring and reacting at 80° C. and 500 rpm for 4 hours to obtain a modified liquid; the weight ratio of the 1,3,5,7-tetramethylcyclotetrasiloxane, 8-chloro-1-octene, octamethylcyclotetrasiloxane, trifluoromethanesulfonic acid, and toluene is 1:1:0.5:0.1:5;
[0092] (4) adding the modifying liquid to the precursor liquid, stirring at 500 rpm at 55-65° C. for 2 h, filtering, and drying to obtain modified potassium titanate whiskers; the weight ratio of the modifying liquid to the precursor liquid is 1:5.
[0093] The preparation method of the organic silicone potting adhesive comprises the following steps:
[0094] The base resin, dimethyl silicone oil-1 and the cross-linking agent are mixed evenly, and then the multi-walled carbon nanotube-1 and the modified potassium titanate whisker are added and mixed evenly, and finally the coupling agent and the catalyst are added and mixed evenly to obtain the silicone potting compound.
[0095] Example 2
[0096] The difference between Example 2 and Example 1 is that the amount of raw materials used is different, and the other aspects are the same.
[0097] A silicone potting adhesive comprises the following components in parts by weight: 100 parts of base resin, 15 parts of dimethyl silicone oil-1, 8 parts of multi-walled carbon nanotube-1, 18 parts of modified potassium titanate whiskers, 3 parts of a cross-linking agent, 4 parts of a coupling agent, and 0.1 parts of a catalyst.
[0098] Example 3
[0099] The difference between Example 3 and Example 1 is that the amount of raw materials used is different, and the other aspects are the same.
[0100] A silicone potting adhesive comprises the following components in parts by weight: 100 parts of base resin, 22 parts of dimethyl silicone oil-1, 12 parts of multi-walled carbon nanotube-1, 12 parts of modified potassium titanate whiskers, 6 parts of a crosslinking agent, 1 part of a coupling agent, and 0.5 parts of a catalyst.
[0101] Example 4
[0102] The difference between Example 4 and Example 1 is that the base resin is different, and the other parts are the same.
[0103] The base resin in this embodiment includes alkoxy-terminated polydimethylsiloxane-1, alkoxy-terminated polydimethylsiloxane-4 and methyl vinyl MQ resin-1 in a mass ratio of 6:3:1.
[0104] Example 5
[0105] The difference between Example 5 and Example 1 is that the base resin is different, and the other parts are the same.
[0106] The base resin in this embodiment includes alkoxy-terminated polydimethylsiloxane-1, alkoxy-terminated polydimethylsiloxane-4 and methyl vinyl MQ resin-1 in a mass ratio of 8:1:1.
[0107] Example 6
[0108] The difference between Example 6 and Example 1 is that the base resin is different, and the other parts are the same.
[0109] The base resin described in this embodiment includes alkoxy-terminated polydimethylsiloxane-2, alkoxy-terminated polydimethylsiloxane-3 and methyl vinyl MQ resin-1 in a mass ratio of 7:2:1.
[0110] Example 7
[0111] The difference between Example 7 and Example 1 is that the base resin is different, and the other parts are the same.
[0112] The base resin described in this embodiment includes alkoxy-terminated polydimethylsiloxane-1, alkoxy-terminated polydimethylsiloxane-4 and methyl vinyl MQ resin-2 in a mass ratio of 7:2:1.
[0113] Example 8
[0114] The difference between Example 8 and Example 1 is that the base resin is different, and the other parts are the same.
[0115] The base resin in this embodiment includes alkoxy-terminated polydimethylsiloxane-1, alkoxy-terminated polydimethylsiloxane-4 and methyl vinyl MQ resin-3 in a mass ratio of 7:2:1.
[0116] Example 9
[0117] The difference between Example 9 and Example 1 is that Example 9 uses an equal amount of dimethyl silicone oil-2 to replace dimethyl silicone oil-1, and the other parts are the same.
[0118] Example 10
[0119] The difference between Example 10 and Example 1 is that Example 10 uses an equal amount of dimethyl silicone oil-3 to replace dimethyl silicone oil-1, and the rest is the same.
[0120] Embodiment 11
[0121] The difference between Example 11 and Example 1 is that Example 11 uses an equal amount of dimethyl silicone oil-4 to replace dimethyl silicone oil-1, and the rest is the same.
[0122] Example 12
[0123] The difference between Example 12 and Example 1 is that Example 12 uses an equal amount of multi-walled carbon nanotube-2 to replace multi-walled carbon nanotube-1, and the rest is the same.
[0124] Example 13
[0125] The difference between Example 13 and Example 1 is that Example 13 uses an equal amount of multi-walled carbon nanotube-3 to replace multi-walled carbon nanotube-1, and the rest is the same.
[0126] Comparative Example 1
[0127] The difference between Comparative Example 1 and Example 1 is that the base resin is different (alkoxy-terminated polydimethylsiloxane-4 is replaced by alkoxy-terminated polydimethylsiloxane-1 in equal amounts), and the rest are the same.
[0128] The base resin of this comparative example includes alkoxy-terminated polydimethylsiloxane-1 and methylvinyl MQ resin-1 in a mass ratio of 9:1.
[0129] Comparative Example 2
[0130] The difference between Comparative Example 2 and Example 1 is that the base resin is different (alkoxy-terminated polydimethylsiloxane-1 is replaced by alkoxy-terminated polydimethylsiloxane-4 in equal amounts), and the rest is the same.
[0131] The base resin of this comparative example includes alkoxy-terminated polydimethylsiloxane-4 and methylvinyl MQ resin-1 in a mass ratio of 9:1.
[0132] Comparative Example 3
[0133] The difference between Comparative Example 3 and Example 1 is that the base resin is different (does not contain methyl vinyl MQ resin), and the other parts are the same.
[0134] The base resin of this comparative example includes alkoxy-terminated polydimethylsiloxane-1 and alkoxy-terminated polydimethylsiloxane-4 in a mass ratio of 7.5:2.5.
[0135] Comparative Example 4
[0136] The difference between Comparative Example 4 and Example 1 is that the base resin is different (alkoxy-terminated polydimethylsiloxane-1 is replaced by alkoxy-terminated polydimethylsiloxane-5 in equal amounts), and the rest is the same.
[0137] The base resin of this comparative example includes alkoxy-terminated polydimethylsiloxane-5, alkoxy-terminated polydimethylsiloxane-4 and methylvinyl MQ resin-1 in a mass ratio of 7:2:1.
[0138] Comparative Example 5
[0139] The difference between Comparative Example 5 and Example 1 is that the base resin is different (alkoxy-terminated polydimethylsiloxane-4 is replaced by alkoxy-terminated polydimethylsiloxane-5 in equal amounts), and the rest is the same.
[0140] The base resin of this comparative example comprises alkoxy-terminated polydimethylsiloxane-1, alkoxy-terminated polydimethylsiloxane-5 and methyl vinyl MQ resin-1 in a mass ratio of 7:2:1.
[0141] Comparative Example 6
[0142] The difference between Comparative Example 6 and Example 1 is that Comparative Example 6 uses an equal amount of potassium titanate whiskers to replace the modified potassium titanate whiskers, and the other contents are the same.
[0143] A silicone potting adhesive comprises the following components in parts by weight: 100 parts of base resin, 20 parts of dimethyl silicone oil-1, 10 parts of multi-walled carbon nanotube-1, 16 parts of potassium titanate whiskers, 5 parts of a crosslinking agent, 2 parts of a coupling agent, and 0.4 parts of a catalyst.
[0144] Comparative Example 7
[0145] The difference between Comparative Example 7 and Example 1 is that the preparation method of the modified potassium titanate whiskers in Comparative Example 7 is different from that in Example 1, and the other parts are the same.
[0146] The preparation method of the modified potassium titanate whisker is:
[0147] (1) stirring potassium titanate whiskers, tartaric acid and 1 mol / L nitric acid solution at a speed of 500 rpm to obtain a mixed solution; the weight ratio of the potassium titanate whiskers, tartaric acid and nitric acid solution is 1:0.15:8;
[0148] (2) adding γ-acryloxypropyltrimethoxysilane to the mixed solution, stirring evenly at 60° C. and 500 rpm, filtering, and drying to obtain modified potassium titanate whiskers; the weight ratio of the γ-acryloxypropyltrimethoxysilane to the mixed solution is 0.04:1.
[0149] Test Case
[0150] Thermal conductivity: Tested according to ASTM D-5470.
[0151] Shear strength: Tested according to GB / T7124-2008
[0152] Table 1
[0153]
[0154]
[0155] It can be seen from Table 1 that the organic silicone potting adhesive of the present invention has excellent thermal conductivity and bonding properties, and can be effectively used in the sealing of electronic components and optical devices.
[0156] By comparing Example 1 with Comparative Examples 1 to 5, it can be seen that the present invention uses the first alkoxy-terminated polydimethylsiloxane, the second alkoxy-terminated polydimethylsiloxane and the methyl vinyl MQ resin in a mass ratio of (6-8):(1-3):1, which effectively improves the thermal conductivity and bonding properties of the sealant.
[0157] By comparing Example 1 with Comparative Examples 6 to 7, it can be seen that the modified potassium titanate whiskers prepared in the present invention can significantly improve thermal conductivity and bonding properties.
[0158] Comparative Examples 1, 7 to 8 show that the present invention uses methyl vinyl MQ resin with a viscosity of 10000 to 15000 mPa·s to further improve thermal conductivity and bonding properties.
[0159] Comparative Examples 1, 9 to 11 show that the present invention uses dimethyl silicone oil with a viscosity of 350 to 700 mPa·s as a plasticizer, which further improves the thermal conductivity and bonding properties.
[0160] By comparing Examples 1 and 12 to 13, it can be seen that the present invention uses multi-walled carbon nanotubes with an outer diameter of 10 to 20 nm and a length of 10 to 30 μm, which further improves the thermal conductivity and bonding properties.
[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A silicone potting compound, characterized in that: The invention comprises the following components in parts by weight: 100 parts of base resin, 15 to 22 parts of plasticizer, 8 to 12 parts of multi-walled carbon nanotubes, 12 to 18 parts of modified potassium titanate whiskers, 3 to 6 parts of crosslinking agent, 1 to 4 parts of coupling agent, and 0.1 to 0.5 parts of catalyst; The base resin comprises a first alkoxy-terminated polydimethylsiloxane, a second alkoxy-terminated polydimethylsiloxane and a methyl vinyl MQ resin in a mass ratio of (6-8):(1-3):1; The viscosity of the first alkoxy-terminated polydimethylsiloxane is AmPa·s, and the viscosity of the second alkoxy-terminated polydimethylsiloxane is BmPa·s, satisfying 6≤A / B≤20.
2. The organic silicone potting adhesive according to claim 1, characterized in that: The viscosity of the first alkoxy-terminated polydimethylsiloxane at 25° C. is 10000 to 20000 mPa·s.
3. The organic silicone potting adhesive according to claim 1, characterized in that: The viscosity BmPa·s of the second alkoxy-terminated polydimethylsiloxane at 25° C. is 1000 to 1500 mPa·s.
4. The organic silicone potting adhesive according to claim 1, characterized in that: The viscosity of the methyl vinyl MQ resin at 25° C. is 10000 to 15000 mPa·s.
5. The organic silicone potting adhesive according to claim 1, characterized in that: The plasticizer is dimethyl silicone oil, and the viscosity of the dimethyl silicone oil at 25° C. is 350-700 mPa·s.
6. The organic silicone potting adhesive according to claim 1, characterized in that: The outer diameter of the multi-walled carbon nanotube is 10-20 nm, and the length is 10-30 μm.
7. The organic silicone potting adhesive according to claim 1, characterized in that: The preparation method of the modified potassium titanate whisker is: (1) stirring potassium titanate whiskers, tartaric acid and nitric acid solution to obtain a mixed solution; (2) adding γ-acryloxypropyltrimethoxysilane to the mixed solution, stirring evenly at 50-70° C. to obtain a precursor solution; (3) adding 1,3,5,7-tetramethylcyclotetrasiloxane, 8-chloro-1-octene, octamethylcyclotetrasiloxane and trifluoromethanesulfonic acid to toluene, stirring and reacting at 70-85° C. for 2-5 hours to obtain a modified solution; (4) Add the modified liquid to the precursor liquid, stir evenly at 55-65° C., filter, and dry to obtain modified potassium titanate whiskers.
8. The organic silicone potting adhesive according to claim 7, characterized in that: The weight ratio of the potassium titanate whisker, tartaric acid and nitric acid solution is 1:(0.1-0.2):(4-10); The weight ratio of the γ-acryloxypropyltrimethoxysilane to the mixed liquid is (0.02-0.05):1; The weight ratio of 1,3,5,7-tetramethylcyclotetrasiloxane, 8-chloro-1-octene, octamethylcyclotetrasiloxane, trifluoromethanesulfonic acid and toluene is 1: (0.5-2): (0.2-0.6): (0.05-0.2): (4-10); The weight ratio of the modifying liquid to the precursor liquid is 1:(4-6).
9. The organic silicone potting adhesive according to claim 1, characterized in that: The crosslinking agent includes at least one of methyl tributylacetoximate silane, phenyl tributylacetoximate silane, and methyl vinyl dibutyl ketone oxime silane; The catalyst includes at least one of dibutyltin dilaurate, dibutyltin diacetate, and stannous octoate; The coupling agent includes at least one of γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.
10. The method for preparing the silicone potting compound according to any one of claims 1 to 9, characterized in that: The following steps are involved: The base resin, plasticizer and cross-linking agent are mixed evenly, and then multi-walled carbon nanotubes and modified potassium titanate whiskers are added and mixed evenly. Finally, a coupling agent and a catalyst are added and mixed evenly to obtain an organic silicone potting adhesive.
11. Use of the organosilicon potting adhesive according to any one of claims 1 to 9 in electronic components and optical devices.
